Methods of Concentrating Stallion Semen - Alvarenga, Marco Antonio [UNESP]; Papa, Frederico Ozanam [UNESP]; Carmo, Marcio T. [UNESP]; Kievitsbosch, Tathiane [UNESP]; Castro Chaves M S, Maria Manoela B. [UNESP]; Ramires Neto, Carlos (Elsevier B.V., 2012)
Removal of excess seminal plasma is sometimes necessary to increase the quality and the longevity of cooled equine semen; moreover, this procedure is an indispensable step aiming to concentrate the sperm cells before freezing equine semen. Typically, the removal of seminal plasma is achieved by centrifugation; however, studies have shown that the force and duration of centrifugation can damage sperm cells and reduce the sperm recovery rate. Recently, new methodologies, such as cushion and filtration, have been described that aim to decrease the mechanical damage of centrifugation to sperm cells. This study aims to compare different methods for concentrating stallion semen.
Keywords: Stallion; Seminal plasma; Semen concentration methods